Volatility index and the return–volatility relation: Intraday evidence from Chinese options market. Issue 11 (9th May 2019) - Li, Jupeng; Yu, Xiaoli; Luo, Xingguo
Abstract: We use unique intraday data to investigate the validity of the Shanghai Stock Exchange's the revised Chinese implied volatility index (iVX). We find that iVX is an effective barometer for the underlying exchange‐traded fund (ETF) market and can be used as a valid "fear index" when there is anxiety over large drops. Furthermore, we use robust quantile regressions and document the asymmetric relation between returns and iVX changes. We also show that behavioral theories offer better explanations for this asymmetric relation than do fundamental theories. More important, we examine the role of iVX in selecting trading strategies.